1998
DOI: 10.1123/tsp.12.1.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Imagery-Manipulated Appraisal on Intensity and Direction of Competitive Anxiety

Abstract: This study attempted to manipulate an athlete’s facilitative or debilitative appraisal (direction; Jones, 1995) of competitive anxiety through imagery-based interventions in order to study the effects on subsequent anxiety intensity (heart rate and CSAI-2) and direction (CSAI-2D; Jones & Swain, 1992). In a within-subjects’ design, 24 experienced soccer players were relaxed via progressive relaxation audiotape and then randomly underwent an imagery-based video- and audiotaped manipulation of their appraisal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 0 publications
4
28
0
Order By: Relevance
“…Consistent with Hale and Whitehouse (1998), a greater intensity of cognitive anxiety was experienced during the threat script compared with the challenge script. It is suggested that a greater cognitive intensity was experienced during the threat scenario due to the script containing more thoughts of concern and worry (e.g., ".…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Consistent with Hale and Whitehouse (1998), a greater intensity of cognitive anxiety was experienced during the threat script compared with the challenge script. It is suggested that a greater cognitive intensity was experienced during the threat scenario due to the script containing more thoughts of concern and worry (e.g., ".…”
Section: Discussionsupporting
confidence: 58%
“…As expected, anxiety symptoms were perceived as more facilitative to the upcoming performance during this scenario. The absence of imaged physical activity more conclusively supports Hale and Whitehouse's (1998) findings that a challenge-or threat-appraised state will elicit increased HR (Jones et al, 2009). Increased HR during the scenarios describing elevated physiological responses supports Lang's (1979) assumption that responses will reflect the actual situation.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…2004 -2007 9, 10, 13, 16, 19, 20, 25 7 (25) • 2008 -2012 3, 4, 5, 6, 8, 11, 12, 14, 15, 17, 18, 21, 16 (57. Studies' reference numbers: 1 (Blair, Hall, & Leyshon, 1993); 2 (Brobst & Ward, 2002); 3 (Burton, Gillham, & Glenn, 2011); 4 (Edvardsson, Ivarsson, & Johnson, 2012); 5 (Gucciardi, Gordon, & Dimmock, 2009a); 6 (Gucciardi, Gordon, & Dimmock, 2009b); 7 (Hale & Whitehouse, 1998);8 (Hashim & Yusof, 2011);9 (Johnson, Hrycaiko, Johnson, & Halas, 2004);10 (Jordet, 2005); 11 (Kerkez, Kulak, & Aktas, 2012); 12 ( Maitland & Grevis, 2010 (Sadeghi, Omar-Fauzee, Jamalis, Ab-Latif, & Cheric, 2010); 23 (Salmon, Hall, & Haslam, 1994); 24 (Seif-Barghi, Kordi, Memari, Ali-Mansournia, & Jalali-Ghomi, 2012); 25 (Thelwell, Greenlees, & Weston, 2006); 26 (Thelwell, Greenlees, & Weston, 2010); 27 (Veraksa & Gorovaya, 2012); 28 (Voight & Callaghan, 2001) www.ccsenet.org/res Vol. 5, No.…”
Section: Search Strategymentioning
confidence: 99%